IMPROVING ABILITY TO KNOW LETTERS THROUGH MOVEMENT AND SONG VIDEO SHOWS OF 4-5 YEARS OLD - Siti Khodijah; Siti Wahyuningsih; Upik Elok Endang Rasmani (Early Childhood Education and Development Journal, 2019)
This study aimed to improve the ability to recognize letters in children aged 4-5 years through motion video and song. The type of this study was a classroom action research were conducted in two cycles. Data collection techniques used observation, interviews, test, and documentation. Quantitative data analysis techniques used comparative data analysis, and qualitative data analysis used interactive model analysis. The validity of quantitative data used construct validity, while the validity test of qualitative data using triangulation and triangulation techniques. The results showed there is an increased ability to recognize letters that can be viewed through an increase in the percentage of completeness that in the first cycle of 65% and the second cycle by 82%.The increase was evidenced by the child's success in imitating / create form letters b,d,p,q,l,i, pronounce letter sounds b,d,p,q,l,i and distinguish the shape of the letter b and d, p and q, l and i. The conclusion of this study is the impression of motion video and song can improve the ability to recognize letters in children aged 4-5 years.